2017
DOI: 10.1111/1467-9566.12615
|View full text |Cite
|
Sign up to set email alerts
|

On the character and production of ‘active participation’ in neuro‐rehabilitation: an Actor‐Network perspective

Abstract: The importance of patients' active involvement in neuro-rehabilitation after acquired brain injury has been consistently emphasised in recent years. However, most approaches fail to show how 'active participation' is practically enacted, focusing on individualised explanations of patient choice and behaviours, or notions of inherent patient traits. Using actor-network theory (ANT) as a sensitising concept, we investigated neuro-rehabilitation practices, asking how participation is shaped through biological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…see Twigg and Buse, 2013). These alternative ways to frame the co-construction of health and social care in PCC may be considered to have significant potential for the development of personalized care environments, and for the development of more adequate and nuanced understandings of the patient as person and expert in conditions of multi-morbidity, moving between the various “collectives” of professional care (see Horton et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…see Twigg and Buse, 2013). These alternative ways to frame the co-construction of health and social care in PCC may be considered to have significant potential for the development of personalized care environments, and for the development of more adequate and nuanced understandings of the patient as person and expert in conditions of multi-morbidity, moving between the various “collectives” of professional care (see Horton et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Sundin & Jansson (2003: 111), for example show how appreciation and respect for PWA may be embodied through nurses' "acting at the same pace and in mutuality with the patient" in a process of continuous adjustment. Horton et al, (2017) have shown how in conceiving rehabilitation as a set of 'collectives', consisting of bodies, objects and technologies "loss and recovery of self can be observed in the accomplishment of these ongoing heterogeneous arrangements" (p.1538). This expanded way of knowing is well suited to the provision of humanly sensitive care in complex cultures of service provision, where competing priorities can undermine staff wellbeing and a sustained capacity to care (Galvin and Todres, 2012).…”
Section: How Are They Learning?mentioning
confidence: 99%
“…We did not assign a priori responsibilities and accountabilities to either nurses' individual awareness of risky body movements or the technology's affordances (Horton et al . ). For us, the failure to prevent in‐hospital falls is not to be found in either the staff, the technology, the mode of observation, or any other actor entangled within this phenomenon.…”
Section: Introductionmentioning
confidence: 97%